2004
DOI: 10.1520/jfs2003196
|View full text |Cite
|
Sign up to set email alerts
|

The Application of an Automated Allele Concordance Analysis System (Compare CallsSM) to Ensure the Accuracy of Single-Source STR DNA Profiles

Abstract: A powerful method for validating a scientific result is to confirm specific results utilizing independent methodologies and processing pathways. Thus, we have designed, developed and validated an automated allele concordance analysis system (CompareCallSM, patent pending) that performs comparisons between two independent DNA analysis platforms to ensure the highest accuracy for allele calls. Application of this system in a quality assurance role has shown the potential to eliminate greater than 90% of the STR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…In a comparison of alleles calls from 2048 STR profiles between manual review with Genotyper and automated review with TrueAllele, only one significant difference was observed when the analyst using Genotyper interpreted a spike as a DNA peak at D8S1179, but TrueAllele correctly designated it as a spike (85). Validation studies with 290 676 STR markers found CompareCalls SM software, an automated allele concordance analysis system from Myriad Genetics, to be at least as accurate as 100% human technical review of STR profiles (86).…”
mentioning
confidence: 99%
“…In a comparison of alleles calls from 2048 STR profiles between manual review with Genotyper and automated review with TrueAllele, only one significant difference was observed when the analyst using Genotyper interpreted a spike as a DNA peak at D8S1179, but TrueAllele correctly designated it as a spike (85). Validation studies with 290 676 STR markers found CompareCalls SM software, an automated allele concordance analysis system from Myriad Genetics, to be at least as accurate as 100% human technical review of STR profiles (86).…”
mentioning
confidence: 99%